IDENTIFIKASI PENERAPAN PENDEKATAN SAINTIFIK KEGIATAN MENANYA (M2) KURIKULUM 2013 DALAM PROSES PEMBELAJARAN MATEMATIKA YANG BERSIFAT TEACHER CENTERED LEARNING - Haryanto, Haryanto; Manalu, Etty Octaviani; Wyrasti, Andi F; Juli, Petrus (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2020)
This Research aims to identify the application of saintific approaches of 2013 curriculum in mathematics learning process which is TCL (Teacher Centered Learning).This is a qualitative research. Data collecting technique of this research was using instrument of observation of the learning process, interview conducted to the teacher and also students and documentation in the form of video recording during learning. The data analysis technique that used in this research was qualitative descriptive analysis. Based on the results of this research we identified a scientific approach second activities Asking (M2) then devided again into 6 indicators and 22 descriptors. At the first learning was obtain 5 indicators and 8 descriptors during the learning process. Then at the second learning was obtain 6 indicators and 15 descriptors during the learning process.